Uma solução para gerenciamento de sistemas em linux. - Soares, Andrey (2001)
This work consists of a study of a model of network management using the SNMP architecture. The SNMP architecture is divided into Agent and M anagement applications, and in this paper the application called Agent will receive more attention.. The aspects worked in this paper start with the management functions and the necessity of MIB until the MIB definition and criation. The result, was the MI B definition that has the objective of storaging information about the hardware and Software inventary at workstations. It is also is presented the next steps of this work, where will be used the XML as language contents, where the objective is mapping MIB to XML.